Reestablishing Paepalanthus babyloniensis (Paepalanthoideae, Eriocaulaceae): taxonomic, anatomical, and chemical evidence - Silva, Lucas Espindola Florêncio Da; Ramos, Renato; Tajima, Aline Sayuri; Teixeira, Andrew Magno; Gomes, Paulo Wender P.; Borges, Ricardo M.; Coan, Alessandra Ike; Trovó, Marcelo (Phytotaxa, 2025)
The status of species for Paepalanthus babyloniensis is formally reinstated here. This species is endemic to the campos rupestres of the Chapadão da Babilônia, within the Serra da Canastra National Park, in the state of Minas Gerais. It is distinguished from the closely related species, P. flaccidus and P. trichophyllus, primarily by characters related to the internodes, the leaf insertion, shape, and pilosity, as well as the shape of the involucral and floral bracts. Besides the general morphology, we also provide a comparative analysis of the anatomy and chemical profile of P. babyloniensis, P. flaccidus, and P. trichophyllus that supports the recognition of the three entities as distinct taxa. A detailed redescription of the taxon, a geographic distribution map, photographs of vegetative and reproductive structures, and comments on the taxonomy of the species are provided.